PENDAMPINGAN REVITALISASI PERPUSTAKAAN DALAM MENDUKUNG GERAKAN LITERASI SEKOLAH - Luthfatul Qibtiyah; Nurul Hidayati; Abdul Kirom (ABDINA: Jurnal Sosial dan Pengabdian kepada Masyarakat, 2022)
The purpose of the library revitalization mentoring activity which is part of community service is to restore the library's function as it should. This mentoring activity was carried out at SDN Batokarang 1, Batu Karang Village, Camplong, Sampang. This activity involved a group of P2M students at the Dirosat Islamiyah Institute Al-Amien Prenduan, Lecturers at SDN Batokarang 1, Librarians at the Regional Library of Sampang Regency, and all students at SDN Batokarang 1. The approach in community service through mentoring activities using the ABCD pattern. This approach emphasizes the empowerment and development of assets in the community. In implementing ABCD-based programs, we are obliged to explore the availability of social assets owned by the community. Synchronization between the availability of social assets and our work programs is a key to the success of ABCD. The result of these activities is the physical improvement of the library space and socialization to the academic community of SDN Batokarang 1 regarding the use of the school library. From the library revitalization activities that we accompanied, it was quite encouraging, at the library launching and socialization related to the use of the library which was filled by the Sampang Regency Regional Library staff, the school residents of SDN Batokarang 1 were happy and very enthusiastic about participating in the socialization event.